International corporate governance after Sarbanes-Oxley (John Wiley & Sons, 2006)
In this book, editors Paul Ali and Greg Gregoriou bring together some of the world's top experts on corporate governance. These experts—each of whom have contributed papers on the impact of the Sarbanes-Oxley Act (and legislation influenced by it) on corporate governance worldwide—share their in-depth insights and knowledge of this topic to help you to navigate the complex field of international corporate governance.